Pengaruh Promosi Penjualan dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Caffe Jetto Brebes - Hendri Sucipto (CV. Ulil Albab Corp, 2024)
Café is one of the most popular places among young people in this modern era. Cafe business people are competing to improve their performance in order to compete with other café entrepreneurs. Business actors must pay attention to factors that affect consumer satisfaction. The purpose of this study is to determine the effect of promotion quality and service quality on customer satisfaction at Caffe Jetto Brebes. The population in this study was all consumers at Caffe Jetto Brebes amounting to 600 respondents. The sampling technique with the Slovin formula was obtained by 86 respondents. The results of this study stated that there is an influence of sales promotion on consumer satisfaction, there is a significant influence of service quality variables on consumer satisfaction, there is a simultaneous influence of sales promotion and service quality on customer satisfaction at Caffe Jetto Brebes.